From optimal control problems to foliations, some kinds of multifoliations and relations to generalised jets - Miroslav, Kures (Penerbit Universiti Kebangsaan Malaysia, 2010)
Transversal foliations and jets modulo foliations are studied. It is shown that multifoliations provides a way for a more general description of (R; S;Q)-jets